2020
DOI: 10.1293/tox.2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological significance of microRNA-210 expression in acute peripheral ischemia in a murine femoral artery ligation model

Abstract: Under hypoxic conditions, microRNA-210 is upregulated and plays multiple physiological roles including in cell growth arrest, stem cell survival, repression of mitochondrial respiration, angiogenesis, and arrest of DNA repair. In this study, we investigated the histopathological expression of microRNA-210 under hypoxic conditions using a femoral artery ligation model established in C57BL/6J mice to determine the pathological significance of microRNA-210. Following femoral artery ligation, ischemia was represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
2
1
Order By: Relevance
“…Moreover, in this study, the existence of muscular necrosis/degeneration and a few cases of minimal hemorrhage indicated the possibility of focal hypoxia, which could be partially related to the increased expression of Hif1α. However, its contribution was considered less dominant than that observed in the hindlimb ischemia model, wherein a severe reduction in blood flow was noted after arterial ligation 7 , whereas no other histopathological findings indicating circulation impairment were noted in the intact area of the treated muscles in this study. Under hypoxic conditions, HIF-1α can continuously act as a transcriptional factor after transfer to the nucleus, and miRNA-210 expression can be upregulated thereafter 1,33 .…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Moreover, in this study, the existence of muscular necrosis/degeneration and a few cases of minimal hemorrhage indicated the possibility of focal hypoxia, which could be partially related to the increased expression of Hif1α. However, its contribution was considered less dominant than that observed in the hindlimb ischemia model, wherein a severe reduction in blood flow was noted after arterial ligation 7 , whereas no other histopathological findings indicating circulation impairment were noted in the intact area of the treated muscles in this study. Under hypoxic conditions, HIF-1α can continuously act as a transcriptional factor after transfer to the nucleus, and miRNA-210 expression can be upregulated thereafter 1,33 .…”
Section: Discussioncontrasting
confidence: 72%
“…Upon the expression of HIF, several microRNAs (miRNAs) are upregulated and miR-210 is one of the major hypoxia-inducible miRNAs. 1 miRNA-210 is reported to be highly expressed under hypoxic conditions, such as in the cardiovascular system 3 , brain 4 , skin 5,6 , and tumor tissues 1 , and increased miRNA-210 expression was observed in a peripheral ischemic mouse skeletal muscular injury model 7 . In our previous study, miRNA-210 expression was observed in myoblasts and macrophages 3 days after ischemic muscular injury, indicating its association with muscular regeneration 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation